Radical cation stabilization in a cucurbituril oligoaniline rotaxane. - Eelkema, R; Maeda, K; Odell, B; Anderson, H (2007)
A cucurbituril-encapsulated oligoaniline rotaxane is synthesized in high yield by reductive amination in aqueous acid. Spectroscopic and electrochemical measurements show that encapsulation by cucurbit[7]uril increases the thermodynamic and kinetic stability of the radical cation of the threaded oligoaniline. This radical cation has a stoichiometry similar to that of the conducting emeraldine salt form of polyaniline, which implies that cucurbituril insulation of polyaniline might drastically alter the oxidation potential of the threaded conjugated polymer chain. Copyright © 2007 American Chemical Society.